2012
DOI: 10.1007/s11999-011-2149-7
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Examinations of Arthroplasty Specimens are not Cost-effective: A Retrospective Cohort Study

Abstract: Background Many hospitals require all operative specimens be sent to pathologists for routine examination. Although previous studies indicate this practice increases medical cost, it remains unclear whether it alters patient management and whether it is cost-effective. Questions/purposes We therefore (1) determined the rate of discordance between clinical and histologic examinations of routine operative specimens during elective primary arthroplasties, (2) determined the cost of routine histologic screening, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 18 publications
3
47
0
Order By: Relevance
“…They estimated that the cost per discrepant diagnosis was $4383, and the cost per discordant diagnosis $122,728. A more recent study [8] found a 2.1% discrepant rate with a cost estimate of $4983 per case, nearly the same amount as Kocher et al [1] No discordant cases were found in this study; however, there was less medical follow-up of cases, as this was focused mainly on medical economics. A separate retrospective analysis of 2144 cases, limited to shoulder arthroscopy [2], showed no discordant pathologic diagnoses when compared to the clinical diagnosis.…”
Section: Review On Orthopedic Surgical Specimenssupporting
confidence: 74%
“…They estimated that the cost per discrepant diagnosis was $4383, and the cost per discordant diagnosis $122,728. A more recent study [8] found a 2.1% discrepant rate with a cost estimate of $4983 per case, nearly the same amount as Kocher et al [1] No discordant cases were found in this study; however, there was less medical follow-up of cases, as this was focused mainly on medical economics. A separate retrospective analysis of 2144 cases, limited to shoulder arthroscopy [2], showed no discordant pathologic diagnoses when compared to the clinical diagnosis.…”
Section: Review On Orthopedic Surgical Specimenssupporting
confidence: 74%
“…Previous studies have demonstrated extremely low diagnostic value and high costs of histological examinations following a variety of procedures, including thumb, knee, and hip arthroplasty; lumbar and cervical discectomy; hallux valgus surgery; wrist ganglion excision; and shoulder and knee arthroscopy [6][7][8][9][10][11][12][13][14][15][16][17][18][19][23][24][25][26][27][28] (see Appendix). While these represent various procedures under different settings, different clinical and histological diagnoses occurred in 0% to 9% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 8039 total hip and knee arthroplasties (5874 total knee arthroplasties and 2165 total hip arthroplasties), an accumulation of studies, each with different specific protocols, demonstrated only two discordant diagnoses (0.025%) [6][7][8][9][10]25 . One was incorrectly determined to be osteomyelitis via histological analysis 6 , and the second was an unexpected and unexplained granulomatous inflammation, which required solely medical follow-up 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations